2012
DOI: 10.1111/j.1432-2277.2012.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of metabolic syndrome: predicting new-onset diabetes, coronary heart disease, and allograft failure late after kidney transplant

Abstract: Summary Metabolic syndrome is associated with coronary heart disease (CHD) and new‐onset diabetes after kidney transplant (NODAT). Using data collected from transplant centers worldwide for the Patient Outcomes in Renal Transplantation study, we examined associations of metabolic syndrome (n = 2253 excluding recipients with diabetes pretransplant), CHD (n = 2253), and NODAT (n = 1840 further excluding recipients with diabetes in the first year post‐transplant), with the primary outcome of allograft failure. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 38 publications
4
37
2
3
Order By: Relevance
“…Novel targets continue to be identified, incorporating an improved understanding of metabolic syndrome and identification of select genetic polymorphisms as PTDM risk factors. Israni et al (26) found posttransplant metabolic syndrome independently associated with subsequent risk of PTDM. When occurring pretransplantation, the metabolic syndrome (27) and its components such as pretransplant hypertriglyceridemia and BMI (28), as well as prediabetes (17) have predicted increased risk for PTDM.…”
Section: Recommendation 4: Identify Patients At Risk For Ptdmmentioning
confidence: 99%
“…Novel targets continue to be identified, incorporating an improved understanding of metabolic syndrome and identification of select genetic polymorphisms as PTDM risk factors. Israni et al (26) found posttransplant metabolic syndrome independently associated with subsequent risk of PTDM. When occurring pretransplantation, the metabolic syndrome (27) and its components such as pretransplant hypertriglyceridemia and BMI (28), as well as prediabetes (17) have predicted increased risk for PTDM.…”
Section: Recommendation 4: Identify Patients At Risk For Ptdmmentioning
confidence: 99%
“…Even though some of these factors also define metabolic syndrome, the specific role of metabolic syndrome in the development of diabetes has not been completely clarified yet. However, three recently published studies have shed some light on this matter, showing that diagnosis of metabolic syndrome after renal transplant23,24 and within the month prior to transplant25 was associated with an increased risk of NODAT.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity in RTRs is strongly linked to the development of metabolic syndrome, with around 60% of patients meeting the diagnostic criteria [103] at transplantation and 9%63% in the subsequent years [104,105] . It is independently associated with longterm graft function and is a prominent risk for allograft failure [105] and CV events secondary to atherosclerosis [106] . The cumulative incidence of coronary heart disease events by 60 mo posttransplant was 5.9% in transplant recipients with metabolic syndrome, compared with 2.3% in recipients without metabolic syndrome.…”
Section: Lifestyle Factorsmentioning
confidence: 99%